Socioeconomic disparities in alcohol-related depression: a national cohort study of low-income medical aid beneficiaries and national health insurance beneficiaries in Korea - Su Kyoung Lee; Yong Jin Kwon (BMC, 2024)
Abstract Objective To examine the association between patterns of alcohol consumption in the past and the risk of depression among medical aid beneficiaries and National Health Insurance beneficiaries in Korea. Methods We used data from the National Health Information Database (NHID) of 1,292,618 participants who underwent health checkups in 2015-16 and 2017-18. We categorized alcohol consumption into four groups: continuous high, increased, decreased, and non-consumers. We followed the participants from 2019 to 2021 and identified new episodes of depression. We calculated adjusted odds ratios (aOR) and 95% confidence intervals (CI) for depression by alcohol consumption groups and socioeconomic status. Results Medical aid beneficiaries had higher risks of depression than National Health Insurance beneficiaries across all alcohol consumption groups. The highest risk was observed among continuous high consumers (aOR, 2.31; 95% CI, 1.36-3.93), followed by increased (aOR, 1.51; 95% CI, 1.17-1.94), decreased (aOR, 1.48; 95% CI, 1.18-1.84), and non-consumers (aOR, 1.37; 95% CI, 1.22-1.54). Conclusions Socioeconomic status and patterns of alcohol consumption in the past are associated with the risk of depression. Public health interventions should consider both factors to reduce alcohol-related depression and health inequalities.